Performances Analysis of Exports and Imports of Livestock Commodities in South Sulawesi - M. Ridwan; I. M. Saleh; A. Fitriani (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2010)
This research aim was to evaluate performance of South Sulawesi Province in the implementation of export and import of livestock commodities using such indicators asthe value of export and import, the share value of export, trade balance and ratio. The study was conducted in the Department of Industry and Trade, the Center Statistics Agency, and the Customs and Excise Duty of Makassarusing a combinaton of interview method and literature review.Research results showed that export import performance has improved as indicated by an increase export volume andvalue of livestock commodities, a decrease import volume and value of livestock commodities.The positive trade balance was an indicator of trade domination of livestock commodities, and fluctuated ratio of trading with a tendency to increase. One aspectthat did not show an improvement compared to other non-oil export value of South Sulawesi was export share of livestock commodities.